Lamb production responses to grass grazing in a companion crop system with corn silage and oversowing of yellow oat in a tropical region. (February 2017) - Pariz, Cristiano M.; Costa, Ciniro; Crusciol, Carlos A.C.; Castilhos, André M.; Meirelles, Paulo R.L.; Roça, Roberto O.; Pinheiro, Rafael S.B.; Kuwahara, Frank A.; Martello, Jorge M.; Cavasano, Francielli A.; Yasuoka, Júnior I.; Sarto, Jaqueline R.W.; et al.
Abstract: Integrated crop-livestock systems in regions with dry winters could be a viable option to increase food production during periods of irregular rain and reduced pasture availability. A corn ( Zea mays L.) silage production system with cover crops of (a) the weedy growth of signal grass [ Urochloa decumbens (Stapf) R. Webster "Basilisk"] and (b) palisade grass [ Urochloa brizantha (Hochst. ex A. Rich.) R. Webster 'Marandu' and 'Piatã'], both with a 0.20- and 0.45-m silage cutting height, was employed in the summer and autumn. Yellow oat ( Avena byzantina cv. São Carlos) was oversown in these systems in the winter and spring. The pasture production, the daily ration intake, the performance and carcass characteristics of lambs ( Ovis aries ) grazing these pastures in a semi-feedlot system (supplemented with silage and concentrate), and the revenue were investigated. The experiment was repeated in the same location for two growing seasons (2010–2011 and 2011–2012) on a Typic Haplorthox in Botucatu, São Paulo, Brazil. Analyzing the system as a whole, intercropping corn silage with palisade grass cv. Marandu (followed by palisade grass cv. Piatã) with a cutting height of 0.45 m combined with yellow oat oversowing was the most robust option for enhancing productivity. The pasture formation for lamb finishing in a semi-feedlot system, the reduction of silage and concentrate intake, and greater live weight and carcass gains per hectare were key attributes for improving the economic viability of this integrated crop-livestock system. Thus, these crop systems were a viable option for the diversification of agricultural activities in tropical regions. Highlights: We investigated a corn silage production with cover crops in the summer/autumn. Yellow oat was oversown in the winter/spring. Greater lamb's carcass gains improved the economic viability. This system can diversify the agricultural activities in tropical regions.